2011
DOI: 10.5301/jabb.2011.6450
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of aqueous nanocrystalline hydroxyapatite in oral bone regeneration

Abstract: The use of Ostim® as bone regenerating material leads to the formation of a highly suitable implant support consisting exclusively of bone in less than 12 months, i.e. in a remarkably short time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…As mentioned previously the histological findings of this study revealed a significant increase in percentage of new bone in the Ostim group ( P = 0.015). These findings were similar to the results of various research studies which have confirmed high rates of dense cortical and cancellous bone ingrowth into bony defects with the use of Ostim [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As mentioned previously the histological findings of this study revealed a significant increase in percentage of new bone in the Ostim group ( P = 0.015). These findings were similar to the results of various research studies which have confirmed high rates of dense cortical and cancellous bone ingrowth into bony defects with the use of Ostim [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Due to disadvantages and limitations of allografts and xenografts, more attention has been focused on alloplastic materials. It is known that alloplastic materials act as a scaffold with benefits such as availability, ease of manipulation, fewer complications, and high security [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…in a remarkably short time. (32) The result of the present study is also consistent with an article published by Araujo et al who demonstrated that the placement of a biomaterial in an extraction socket will enhance bone modeling and compensate the marginal ridge contraction. (33) Another study recommends that the use of nanobone in extractions operations and bone fractures lead to speed healing.…”
Section: Resultssupporting
confidence: 92%
“…Ostim ® , a nanoparticular HA aqueous paste, has been described as bone-inducible paste. Several publications observed that Ostim ® particles were not fully resorbed 12 weeks post-surgery 9 11 12 34 . In general all HA pastes used in this study were shown to support bone formation.…”
Section: Discussionmentioning
confidence: 99%